2021
DOI: 10.1111/1756-185x.14058
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality persists in patients with rheumatoid arthritis

Abstract: Objectives To investigate the causes and risk of death in a large cohort of Korean patients with rheumatoid arthritis (RA). Methods Patients in the Hanyang BAE (Bae registry of Autoimmune diseases for Epidemiology) RA cohort who fulfilled the American College of Rheumatology criteria were analyzed. A total of 2355 patients were enrolled from October 2001 to December 2015. Mortality data were derived by linking with data from the Korean National Statistical Office. Standardized mortality ratio was estimated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Three studies have reported the mortality rate in Korean patients with RA [9][10][11] (Table 1). The study performed by Lee et al [11] is an extension of the study performed by Kim et al [9] conducted by the same institution. These In addition, many foreign studies have previously confirmed that the mortality rate of individuals with RA is higher than that of the general population.…”
Section: Main Subjects Mortality Rates In Korean Patients With Ramentioning
confidence: 99%
“…Three studies have reported the mortality rate in Korean patients with RA [9][10][11] (Table 1). The study performed by Lee et al [11] is an extension of the study performed by Kim et al [9] conducted by the same institution. These In addition, many foreign studies have previously confirmed that the mortality rate of individuals with RA is higher than that of the general population.…”
Section: Main Subjects Mortality Rates In Korean Patients With Ramentioning
confidence: 99%
“…Our study observed comparable safety incidence rates of joint replacement between the JAKi and TNFi groups. The all‐cause mortality rate of patients with RA has decreased over the past decades; however, it remains higher than that of the general population 25,26 . A few studies have revealed increased mortality in patients treated with cDMARDs but not those treated with bDMARDs.…”
Section: Discussionmentioning
confidence: 99%
“…A report carried out in 1953 showed excess mortality of 29% in patients with RA. 47 In 2021, these data were still worrying and showed a higher mortality rate in RA patients than in the general population, 48 and this mortality increase is due to CVR factors. 49 The pathophysiological pathways in RA cause changes in the patient's metabolism, and CVR increases when adding an unhealthy lifestyle.…”
Section: Cardiovascular Riskmentioning
confidence: 99%
“…A report carried out in 1953 showed excess mortality of 29% in patients with RA. 47 In 2021, these data were still worrying and showed a higher mortality rate in RA patients than in the general population, 48 and this mortality increase is due to CVR factors. 49 …”
Section: Cardiovascular Riskmentioning
confidence: 99%